PENGARUH CELEBRITY ENDORSER, BRAND EQUITY DAN CUSTOMER BONDING TERHADAP TINGKAT INTENSI LOYALITAS PELANGGAN TOKOPEDIA - Harwati, Tan Anna; Aryanto, Vincent Didiek Wiet (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2024)
The aim of this research is to evaluate the influence of celebrity endorsers, Brandequity and customer bondingon Tokopedia customer loyalty. In this research, the population consists of people who have used Tokopedia as a place to shop online at least twice, and the sampel was taken from 150 respondents using non-probability sampling methods, especially purposive. This research uses PLS (Partial Least Square) as an analysis tool. Tokopedia must concentrate on customer loyalty to build Brandequity by considering Brandequity and existing customer connections. The results found that celebrity endorsers had no significant effect on Tokopedia customer loyalty. However, the Brandequity variable has a positive and significant effect on Tokopedia customer loyalty. Customer bonding also has a positive and significant effect on Tokopedia customer loyalty.